2014
DOI: 10.1093/jel/equ018
|View full text |Cite
|
Sign up to set email alerts
|

Science Friction: Antarctic Research Whaling and the International Court of Justice

Abstract: Whaling remains one of the most controversial and divisive aspects of the modern regulation of marine resources. In 1982, the International Whaling Commission, the global management body responsible for the regulation of whale stocks, instituted a moratorium on commercial hunting, which has been in force for almost 20 years. Nevertheless, a number of legal avenues exist within the current international regulatory framework to facilitate a degree of continued hunting. The most contentious of these is the scient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Harrop tracks how the ICRW has evolved from a regime that was initially concerned with supporting the whaling industry, to one that was focused on conservation and is now increasingly adopting a compassionate approach to regulating society's interactions with whales (Harrop 2003 88 et seq). The resulting tensions between anti-and pro-whaling states culminated in the Whaling in the Antarctic (Australia v Japan; New Zealand intervening) case (ICJ 2014), in which the International Court of Justice concluded that Japan's JARPA-II scientific programme, which was viewed by others as a front for commercial whaling due to the scientifically-unjustifiable use of lethal research methods, was unlawful (Caddell 2014). Japan subsequently withdrew from the ICRW and in July 2019 announced that it would recommence commercial whaling, 5 suggesting that the allegations against JARPA-II had some merit.…”
Section: Legal Mechanisms For Conserving Biodiversitymentioning
confidence: 99%
“…Harrop tracks how the ICRW has evolved from a regime that was initially concerned with supporting the whaling industry, to one that was focused on conservation and is now increasingly adopting a compassionate approach to regulating society's interactions with whales (Harrop 2003 88 et seq). The resulting tensions between anti-and pro-whaling states culminated in the Whaling in the Antarctic (Australia v Japan; New Zealand intervening) case (ICJ 2014), in which the International Court of Justice concluded that Japan's JARPA-II scientific programme, which was viewed by others as a front for commercial whaling due to the scientifically-unjustifiable use of lethal research methods, was unlawful (Caddell 2014). Japan subsequently withdrew from the ICRW and in July 2019 announced that it would recommence commercial whaling, 5 suggesting that the allegations against JARPA-II had some merit.…”
Section: Legal Mechanisms For Conserving Biodiversitymentioning
confidence: 99%